Socialization of Smart Communicative Objects in Industrial Internet of Things. Issue 10 (2022) - Kilani, R.; Zouinkhi, A.; Bajic, E.; Abdelkrim, M.N.
Abstract: In the recent past the Internet of Things (IoT) is moving from interactive objects to smart objects. The number of smart devices or sensors built-in becomes larger. The increase in the number of services exchanged between connected objects has led to the creation of a new concept called Social IoT (SIoT), in which heterogeneous or homogeneous objects can interact and request or exchange services, which makes it possible to include social or human actions in the IoT platform. The use of technologies based on the concept of the Internet of Things in applications and industrial sectors has built a new concept of research called the Industrial Internet of Things (IIoT). The integration of the SIoT concept into the Industrial Internet of Things (IIoT) plays an important role in improving system performance in Industry 4.0 and gives rise to the Social Internet of Industrial Things (SIoIT). In this context, we have revealed a new socio-inspired interaction model between industrial communicating objects inspired by sociological approaches that transform objects into socialized industrial communicating objects. These objects form a community, autonomously and dynamically, by exchanging messages to know each other perfectly, and service requests between objects are realized in an adaptive way according to the principles of social interaction governed by socio-inspired strategies and conditions. The model is evaluated using Netlogo multi-agent system simulation environment.